Black women in the marketplace: everyday gender-based risks against Haiti's madan saras (women traders). (1st December 2015) - ,
Abstract : In Haiti, madan saras have for centuries personalised economics through a sistèm pratik that has institutionalised market operations by connecting buyers and sellers. This study – based on 77 interviews, mainly (73%) with madan saras from northern Haiti – exposes gender-based violence (GBV) towards Black women entrepreneurs, examining the views of the madan saras about their work and using the framework of Black feminist theory to contextualise their experience. Despite social awareness of the contributions of madan saras, the pervasive GBV against madan saras in business is ignored by society and policymakers, and Haitian women must contend with these risks by themselves.